Simulation-based education workshop: perceptions of participants - Piryani RM; Piryani S; Shrestha U; Acharya A; Kanskar S; Shahi M; Kayastha J; Chaulagain A; Agarwal JP; Bajracharya SR (Advances in Medical Education and Practice, 2019)
Rano Mal Piryani,1 Suneel Piryani,2 Unisha Shrestha,3 Asmita Acharya,3 Srijana Kanskar,3 Mandira Shahi,4 Jeny Kayastha,5 Amrita Chaulagain,6 Jagdish Prasad Agarwal,7 Sangha Ratna Bajracharya81Health Professions Training Committee, Universal College of Medical Sciences, Bhairahawa, Nepal; 2Department of Community Health Sciences, Aga Khan University, Karachi, Pakistan; 3Simulation Based Education Training, Laerdal Global Health Nepal, Kathmandu, Nepal; 4Maharajganj Nursing Campus and National Centre for Health Professions Education (NCHPE), Institute of Medicine Nepal, Kathmandu, Nepal; 5Orthopaedic Department, St Vincent’s Private Hospital Northside, Brisbane, QLD, Australia; 6Research, Jeebanta Advanced Kathmandu Imaging Private Limited, Kathmandu, Nepal; 7Neurology and Medical Education Training, Tribhuvan University Institute of Medicine, Kathmandu, Nepal; 8Pharmacology and Medical Education, Tribhuvan University Institute of Medicine, Kathmandu, NepalBackground: Simulation-based education (SBE) is increasingly endorsed as an educational strategy. It allows health-care professionals to practice clinical skills within a safe learning environment, and requires devices for simulation or simulated patients, trained teachers, and an appropriate environment. The objective of this study was to evaluate perceptions of participants on SBE and an SBE workshop.Methods: A 1-day SBE workshop was conducted on September 4, 2018, in collaboration with Laerdal Global Health Nepal and the National Centre for Health Professions Education (NCHPE), Institute of Medicine, Kathmandu, Nepal. Semistructured pretest and posttest questionnaires were used to evaluate the perceptions of participants regarding SBE and the effectiveness of the workshop. Data were analyzed using SPSS 21.Results: The mean difference in participant perceptions of SBE before and after participation in the workshop was significant (P<0.05) on seven statements: enhances communication skills (pretest 4.53±0.72, posttest 4.84±0.75; P=0.03), helps in seeing and managing even rarest of cases (pretest 3.59±1.00, posttest 4.21±0.92; P=0.02), overcomes the problem of uncooperative patients (pretest 3.12±0.93, posttest 3.95±1.22; P=0.004), increases confidence of students in dealing with real patients (pretest 4.29±0.77, posttest 4.79±0.42; P=0.041), enables preparation of rating scales for skills and attitude evaluation (pretest 3.76±0.83, posttest 4.11±0.76; P=0.049), provides immediate feedback during simulation (pretest 4.06±0.9, posttest 4.58±0.51; P=0.016), and keeps materials/equipment ready before simulation (pretest 4.29±0.68, posttest 4.79±0.53; P=0.007). Mean scores for participant feedback on the workshop using a Likert scale of 1–5 (5= strongly agree, 1= strongly disagree) were notable: objective of workshop fulfilled (4.16±0.688), session very interesting (4.37±0.597), session useful for future job (4.47±0.513), scenario relevant to subject (4.21±0.787), what I learnt will be useful in practice (4.05±0.78), resource persons/facilitators were helpful and effective (4.37±0.597), professional (4.42±0.507), and answered all questions (4.32±0.478), and course content was presented clearly (4.26±0.452). Almost all participants found the workshop useful and well presented, and suggested conducting such workshops frequently.Conclusion: The SBE workshop produced substantial differences in perceptions of participants. Participants found the workshop effective in improving knowledge and understanding of SBE.Keywords: evaluation, faculty, perception, simulation education, workshop